Peran Kelembagaan dalam Pengembangan Pendidikan Islam di Indonesia - Syaifuddin (TABYIN: JURNAL PENDIDIKAN ISLAM, 2021)
Islamic education has been rapidly growing in Indonesia. This development can be attributed to the diverse institutional roles of Islamic education in the country. Through literature reviews and content analysis of existing literature, it has been discovered that the roots of Islamic education in Indonesia trace back to the introduction of Islam in the region. The dissemination of Islamic education initially began through informal educational institutions like mosques, surau, langar, and similar places, along with the spread of Islamic teachings in general. These informal educational institutions later evolved into non-formal educational institutions, such as Islamic boarding schools (pondok pesantren). Non-formal educational institutions, in turn, developed into formal educational institutions like madrasahs and other Islamic schools. All of these Islamic educational institutions play a vital role in the development of Islamic education in Indonesia. It can be firmly stated that the institutional aspects of Islamic education are crucial for its advancement in the country.